2019
DOI: 10.1186/s12891-019-2995-0
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Short External Rotator Muscles of the Hip

Abstract: BackgroundMuscle architecture, or the arrangement of sarcomeres and fibers within muscles, defines functional capacity. There are limited data that provide an understanding of hip short external rotator muscle architecture. The purpose of this study was thus to characterize the architecture of these small hip muscles.MethodsEight muscles from 10 independent human cadaver hips were used in this study (n = 80 muscles). Architectural measurements were made on pectineus, piriformis, gemelli, obturators, quadratus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The structural property of the hip external rotators suggested that force generation was maximized to act as a single axis of rotation because its pennation angle was almost parallel [ 18 ]. Because of this structural property, the hip external rotators compressed the hip joint along a single axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural property of the hip external rotators suggested that force generation was maximized to act as a single axis of rotation because its pennation angle was almost parallel [ 18 ]. Because of this structural property, the hip external rotators compressed the hip joint along a single axis.…”
Section: Discussionmentioning
confidence: 99%
“…External rotators might act synergistically in vivo to stabilize the hip joint at any hip flexion angle. An anatomical study of external rotators reported that the superior gemellus, obturator internus, inferior gemellus, and obturator externus were essentially fused [ 18 ]. Thus, these external rotators can interact with each other and function as one muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The obturator internus is one of the short external rotators of the hip. It is the longest of the external hip rotators with a length of 13.12 ± 0.27 cm [ 1 ]. It originates from the inferior margin of the superior pubic ramus and from the pelvic surface of the obturator membrane around the obturator foramen.…”
Section: Discussionmentioning
confidence: 99%
“…The obturator internus muscle can be considered as a single functional unit together with the superior and inferior gemellus as well as the obturator externus muscle. All together, they are important stabilizers of the pelvis as they stabilize the femoral head to the acetabulum [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…This group of muscles helps to stabilize the femoral head in the acetabulum during movement and provide a uniform external rotation force despite changes in hip position or muscle length. 9,15 The quadratus femoris arises from the external aspect of the ischial tuberosity and inserts into the trochanteric crest of the femur. The obturator internus arises from the inner surface of the superior pubic ramus and obturator membrane before being reflected at a right angle over the grooved surface of the ischium where it joins the gemelli muscles (triceps coxae) to insert on the greater trochanter as a "conjoint tendon."…”
mentioning
confidence: 99%